Overuse of medical care in paediatrics: A survey from five countries in the European Academy of Pediatrics - Jankauskaite, Lina; Grechukha, Yevgenii; Kjær, Kristin Avranden; Mamenko, Marina; Nakstad, Britt; Romankevych, Ivanna; Schnyder, Sara; Selvakumar, Joel; Trapani, Sandra; Daniliaviciene, Sandra; Valiulis, Arunas; Wyder, Corinne; et al. (Frontiers in Pediatrics, 2022)
Studies and initiatives such as the “Choosing wisely” (CW) campaign emphasise evidence-based investigations and treatment to avoid overdiagnosis and overtreatment. The perception of the extent of medical overactivity among professionals and drivers behind are not well studied in the paediatric field. Aim We aimed to investigate the physicians‘ opinion and clarify the main drivers regarding medical overactivity in member countries of the European Academy of Paediatrics (EAP). Methods In this study, paediatricians, paediatric residents, primary care paediatricians, and family doctors treating children were surveyed in Norway, Lithuania, Ukraine, Italy, and Switzerland. Over-investigation was defined as “diagnostic work-up or referral that is unlikely to provide information which is relevant for a patient” and overtreatment was defined as “treatment that does not benefit or can harm more than benefit the patient.” The original questionnaire was developed in 2018 by a working group from the Norwegian Paediatric Association. Results Overall, 1,416 medical doctors participated in the survey, ranging from 144 in Lithuania to 337 in Switzerland. 83% stated that they experienced over-investigation/overtreatment, and 81% perceived this as a problem. The majority (83%) perceived expectations from family and patients as the most important driver for overtreatment in their country. Other drivers for overuse were use of national guidelines/recommendations, worry for reactions, and reduction of uncertainty. Conclusion This is the first study investigating knowledge and attitude toward medical overactivity in European countries. Despite different cultural and economic environments, the patterns and drivers of increased investigations and medicalisation are similar.